Retinal Vascular Caliber and Kidney Function in Children and Adolescents with Type 1 Diabetes. (4th May 2017) - Keel, Stuart; Itsiopoulos, Catherine; Koklanis, Konstandina; Vukicevic, Meri; Cameron, Fergus; Brazionis, Laima
ABSTRACT: Purpose : To evaluate the relationship between retinal vascular caliber and kidney function in a cohort of Australian children and adolescents with type 1 diabetes. Methods : This was a cross-sectional study of 483 children and adolescents with type 1 diabetes, aged 7–18 years. An audit of medical files of participants who attended the Royal Children's Hospital, Melbourne, between January 2009 and March 2014 was performed. Albumin to creatinine ratio (ACR) was acquired through spot urine samples and microalbuminuria was classified as ACR >3.5 mg/mmol in females and >2.5 mg/mmol in males. Retinal vascular caliber was measured using a standardized protocol and later summarized as central retinal arteriolar equivalent (CRAE) and central retinal venular equivalent (CRVE). Results : CRAE was significantly narrower in participants with microalbuminuria compared to those with normo-albuminuria in crude analysis (mean ± standard deviation 159.07 ± 9.90µm vs 164.49 ± 12.45 µm; p = 0.006). After adjustment for key confounders and known or potential mediators of microalbuminuria (age, sex, ethnicity, hemoglobin A1c, systolic blood pressure, total cholesterol, body mass index, duration of diabetes and CRVE) the association between narrower CRAE and microalbuminuria was attenuated and was no longer significant (95% confidence interval 0.94–1.02, p = 0.222). No significant associations between CRVE or arteriole-to-venule ratio and microalbuminuria were observed in univariate or multivariate models. Conclusions : After adjustment for potential confounding variables, retinal vascular caliber was not significantly associated with microalbuminuria in this sample of children and adolescents with type 1 diabetes. Future prospective longitudinal research is warranted to further evaluate these findings.